Tourism and education in formation of the human capital agency - Fedorchenko, Volodymyr K.; Kutuev, Pavlo V.; Fedorchenko, Nataliіa V.; Vasilets, Olga I. (Linguistics and Culture Review, 2021)
The article is devoted to the issue of mainstreaming the reflexion and the practical use of the educational potential of tourism in the current conditions of societal crisis. The major thesis of the article is that the unique characteristics of the tourism in the context of systemic transformations are crucial for the formation of agency/subjectivity as well as responsible spontaneous nature of human capital. The article emphasises the role of the tourism sector for solving modern historical problems of revising and optimising, as humanisation and elevation, the resource wealth of the human person. The functions of tourism practices that use the specifics of location (nature, personnel, history) to solve global problems via cooperation, especially in the context of technological, biological, and environmental challenges of anthroposociogenesis, are being investigated and reconciled for the sustainable development of society under global risks and uncertainty. Particular attention is paid to the fact that the cultural characteristics of social space are constituted and, at the same time, constitute its symbolic character through communication.